(untitled) (Eurasian Journal of Philology Science and Education, 2020)
he article deals with various types of magical folklore – the ways of development, the definition of the genre nature of the batа, and the specific features and characteristics. The origin of the batа genre is deeply rooted in the past. Because people thought that words had great power. Pronouncing them can attract wealth, happiness, and even material well-being. Conversely, it was believed that the word can be used to punish people who committed evil acts or treachery. It is known that ailments and illnesses were also treated with the help of improvised songs that have magical powers (Baksy saryny). People with naive ideas about the world believed that with the help of songs, you can get rid of not only problems but also many other ailments. They were the basis for the emergence of the genre. Bata is divided into two types: blessing (On Bata) and curse (Teris Bata). On Bata – this is not just a wish for good, here the word is directed to good and creation, teris Bata – was a sign of reverse blessing, blessing with a curse. In the Soviet period, the Bata genre was practically not studied. Therefore, the authors considered this concept comprehensively. We studied the functional and structural features of blessing in a person’s life. It should be noted that the Bata genre that goes back centuries is still an integral part of everyday life. Good words, wishes, and bright intentions are considered the Foundation of human morality at all times.